Planting ratio and plant growth regulators affecting seed quality in CGMS based chilli (Capsicum annuum) hybrid - THAKUR, NEHA; VASUDEVAN, S N; DODDAGOUDAR, S R; TEMBHURNE, B V; I, MACHA S; PATIL, M G (The Indian Journal of Agricultural Sciences, 2022)
In the present study, the seed production was carried out during 2016 and 2017 in the newly released cytoplasmic genetic male sterility (CGMS) based chilli (Capsicum annuum) hybrid. The objective of this study was to enhance the seed quality for newly released hybrid using given treatments in the field. The experiment was conducted at the Department of Seed Science and Technology, University of Agricultural Sciences, Raichur, Karnataka in the laboratory and field conditions. Plant growth regulators (PGRs) target specific receptor molecules in the plant tissue that can certainly transform plant metabolism. Similarly adapting a specific ratio of female and male while planting can check yield and quality constraints in fruit and seed production. Henceforth treatments were decided keeping in view these points. It was found that planting ratio (2:1 was best) and PGR spray (NAA @40 ppm best) significantly promoted the seed quality parameters, viz. germination (%), seedling dry weight (mg), shoot length (cm), seedling vigour index, dehydrogenase enzyme activity and lowered the electrical conductivity (dS/cm) as compared to other treatments. Also, the treatment combination P2S4 (2:1 + NAA @40 ppm) proved to be the best for these seed quality parameters. Thus, the parental lines in 2:1 ratio proved to be best for natural crossing followed by spraying at flower initiation stage with NAA @40 ppm as PGR to obtain higher seed quality in CGMS based chilli hybrid UARChH42 (JCH42). Hence it may be recommended in seed production technology of this hybrid.